O papel dos stakeholders na gestão de riscos em recalls na cadeia de alimentos - Oliveira, Lucas Lima de (2021)
The complexity of food supply chains (FSCs) is one of the factors that increase the vulnerability of companies to internal, external and environmental risks, causing different types of recalls, such as failures in product quality and safety. Recalls increase the risk to human health and have negative effects on all stakeholders, which may adversely affect the company's performance, reduce the brand value, cause losses in revenue and market share, in addition to changing consumer demand and prices in the future market. Since recalls are generally the result of multiple risks, it is necessary to use risk management in the supply chain in order to minimize such incidents in the food industry. Thus, the objective of this study is to analyze what are the different roles of stakeholders in the risk management process in food recall events. In order to explore this problem, a systematic literature review was carried out, and from 83 selected articles, it was identified that 10 stakeholders responsible for 25 risk management actions in a recall process in the FSCs. Then, an empirical research was conducted with different actors involved in recall events in two food industries in Brazil. As a result, it was observed that stakeholders are involved in four phases of food recall management, with 29 risk management actions aimed at preventing, controlling, regulating, and communicating risks. From the results found, an explanatory map was prepared with the risk management actions that each stakeholder performs to prevent or contain the impacts of a recall on the FSCs, and a frame showing which phases of the management of a recall the stakeholders must be present and their respective actions at that given moment. In terms of academic contribution, this research contributes to the literature by exploring the management of recalls at FSCs from the perspective of the theory of stakeholders identifying different needs, obligations and relationships between stakeholders. In terms of managerial contributions, the results can help companies, professionals and health agencies to understand their responsibility and role in the food supply chain, in addition to what moments in the management of recall processes they act to apply the appropriate actions in a way to avoid or limit the impacts of a recall.